Legal Analysis of the International Agreement on Sister City Cooperation Surabaya-Liverpool in Conducting Parallel Diplomacy - Ahmad ‘Amar Al-Gifari; Ayub Torry Satriyo Kusumo; Sri Lestari Rahayu (International Journal of Law, Crime and Justice, 2024)
The sister city international agreement is an implementation of regional autonomy carried out by local governments in conducting parallel diplomacy. The Surabaya City Government seizes this opportunity and, among others, engages in sister city cooperation with Liverpool City. This study addresses the issue of the authority of the Surabaya City Government in making sister city international agreements and examines the strength and position of sister city international agreements in the form of a Memorandum of Understanding (MoU) from the perspective of international law. The type of research used in this study is juridical-normative, thus the approach employed is a statutory approach by examining all statutory regulations related to sister city international agreements. The results of this research indicate that through the analysis of statutory regulations in Indonesia related to international agreements, the Local Government, in this case, the Surabaya City Government, has the authority to make sister city international agreements in an effort to conduct parallel diplomacy with Liverpool City. The position and strength of the sister city international agreement between the Surabaya City Government and Liverpool City in the form of a Memorandum of Understanding (MoU) under international law are a valid international agreement with rights and obligations outlined therein and categorized as a treaty contract that only creates legal implications for the parties involved, namely the Surabaya City Government and Liverpool City.